2007
DOI: 10.1679/aohc.70.135
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of central lacteals in the murine jejunum following ischemia-reperfusion injury

Abstract: The intestinal mucosa is vulnerable to an ischemia-reperfusion (I/R) attendant on some bowel diseases and surgery; thus, the restoration of the mucosal integrity is critical to achieving functional recovery of the intestine injured by I/R. In this histochemical study, we investigated the alteration of the central lacteals--which are essential for the transport of fat, tissue fluid, and immune cells in the intestinal mucosa--in the murine jejunum after I/R. The intestine inflicted with I/R demonstrated mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The vascular recovery of villus BECs and LECs after I/R injury proceeds via a stepwise process in which blood capillaries (BECs) regrow earlier than lacteals (LECs) in the villous stroma 46 . We found that the EC- Foxc -DKO mutation was associated with defective vascular repair of intestinal BECs and LECs after I/R injury (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vascular recovery of villus BECs and LECs after I/R injury proceeds via a stepwise process in which blood capillaries (BECs) regrow earlier than lacteals (LECs) in the villous stroma 46 . We found that the EC- Foxc -DKO mutation was associated with defective vascular repair of intestinal BECs and LECs after I/R injury (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…7). The vascular regrowth of villus BECs and LECs after I/R injury proceeds via a stepwise, interactive process, and regeneration of villus blood vessels precedes reconstruction of lacteals ( 51 ) (Fig. 4, Movies S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, impaired blood vascular recovery of the EC‐ Foxc ‐DKO mice after intestinal I/R injury is rescued by CXCL12 treatment (Fig 10H and I). Since the vascular regrowth of villous BECs and LECs after I/R injury proceeds via a stepwise, interactive process, and regeneration of villus blood vessels precedes the reconstruction of lacteals (Meng et al , 2007) (Fig 4 and Movies EV1 and EV2), the severity of mucosal damage is greater in the EC‐ Foxc ‐DKO mice than in the LEC‐ Foxc ‐DKO mice. Moreover, consistent with the role of the CXCL12/CXCR4 pathway in lymphangiogenesis (Zhuo et al , 2012), impaired lacteal length of the EC‐ Foxc ‐DKO mice after intestinal I/R injury is rescued by CXCL12 treatment (Fig 10H and J).…”
Section: Discussionmentioning
confidence: 99%